Developing cessation interventions for the social and community service setting: A qualitative study of barriers to quitting among disadvantaged Australian smokers - O'Brien Jon; Paul Christine; Bonevski Billie; Bryant Jamie; Oakes Wendy (BMC, 2011)
Abstract Background Smoking rates remain unacceptably high among individuals who are socially disadvantaged. Social and community service organisations (SCSO) are increasingly interested in providing smoking cessation support to clients, however little is known about the best way to assist disadvantaged smokers to quit in this setting. This study aimed to explore barriers and facilitators to quitting within the conceptual framework of the PRECEDE model to identify possible interventions appropriate to the social and community service setting. Methods Semi-structured focus groups were conducted with clients attending five community welfare organisations located in New South Wales, Australia. Thirty-two clients participated in six focus groups. A discussion guide was used to explore the barriers and facilitators to smoking and smoking cessation including: current smoking behaviour, motivation to quit, past quit attempts, barriers to quitting and preferences for cessation support. Focus groups were audio-taped, transcribed and analysed using thematic analysis techniques. Results Participants were current smokers and most expressed a desire to quit. Factors predisposing continued smoking included perceived benefits of smoking for stress relief, doubting of ability to quit, fear of gaining weight, and poor knowledge and scepticism about available quit support. The high cost of nicotine replacement therapy was a barrier to its use. Continual exposure to smoking in personal relationships and in the community reinforced smoking. Participants expressed a strong preference for personalised quit support. Conclusions Disadvantaged smokers in Australia express a desire to quit smoking, but find quitting difficult for a number of reasons. SCSOs may have a role in providing information about the availability of quit support, engaging disadvantaged smokers with available quit support, and providing personalised, ongoing support.